CX3CL1/CX3CR1 axis in liver disease: context-dependent roles and balance - Liu, Jing; Guo, Zhen; Zheng, Xin (Frontiers in Immunology, 2026)
This review provides a systematic and critical examination of the multifaceted roles of the CX3CL1/CX3CR1 axis in liver diseases. We emphasize its context-dependent duality—exhibiting both pro- and anti-inflammatory, pro- and anti-fibrotic, and pro- and anti-tumor functions across different etiologies. Moving beyond a binary good or bad” paradigm, we propose a contextual signaling model that integrates cellular source, microenvironmental cues, and intersecting pathways to explain its divergent roles. We synthesize recent advances in its involvement in NAFLD/NASH, viral hepatitis, autoimmune hepatitis, schistosomiasis, liver fibrosis and hepatocellular carcinoma. The review critically evaluates the axis’s potential as a biomarker, discusses methodological advances and limitations in human studies, and analyzes therapeutic strategies with a focus on translational challenges. We conclude with a forward-looking perspective on precision medicine approaches targeting this axis.